Peru in the doctoral theses of United States: Literature review of the period 1977-1988 - Ortiz, Rodomiro (1990)
The author reviews the doctoral theses on Peru written in universities of the United States, between 1977 and 1988. He also makes a comparative analysis of the subjects, that were studied in this period, in relation with the ones that were studied in previous periods, according to a wellknown study by Héctor Maletta.